Communication to its customers banking: evolution and the alternative model of Islamic banking - de la Orden de la Cruz, Mª del Carmen; Padilla Castillo, Graciela; Sánchez González, Pilar (Historia y Comunicación Social, 2014)
The recent crisis has highlighted the problems of banking communication regarding their customers, exacerbated by the lack of financial education of citizens. Thus, it becomes evident the need for change communication strategy in this sector and the search for new methods and approaches. In this work we analyze the changes in recent years in terms of banking communication and how the Islamic banking could be a reference.